Anticancer Activity of Protein Fungus Xylaria psidii KT30 - Aris Munandar (JURNAL PERIKANAN DAN KELAUTAN, 2015)
Previous research shows that protein of an algicolous fungus Xylaria psidii KT30 inhibited HeLa cell with an average 264.7 μg/mL. To enhance the potent anticancer activity of extracellular protein from Xylaria psidii KT30, the present research demonstrated purification of its secreted protein. Anticancer against Chang cell line (liver cell) and HeLa cell line (cervical cancer) was done by MTT cytotoxic method. Protein concentration assay was done by bicinchoninic acid (BCA) protein assay kit. Anticancer assay showed protein of fungus KT30 was not toxic against Chang cell line and HeLa cell line. Based on calculation, IC50 value protein of fraction ammonium sulfat 90% and fractions 11-12 were 670.86 and 1451.68 µg/mL. The protein concentration of fraction ammonium sulfat 90% and fractions 11-12 were 9.013 and 0.604 mg/mL.